2023
DOI: 10.1038/s41467-023-39246-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and definitive treatment of phenylketonuria in variant-humanized mice with corrective editing

Abstract: Phenylketonuria (PKU), an autosomal recessive disorder caused by pathogenic variants in the phenylalanine hydroxylase (PAH) gene, results in the accumulation of blood phenylalanine (Phe) to neurotoxic levels. Current dietary and medical treatments are chronic and reduce, rather than normalize, blood Phe levels. Among the most frequently occurring PAH variants in PKU patients is the P281L (c.842C>T) variant. Using a CRISPR prime-edited hepatocyte cell line and a humanized PKU mouse model, we demonstrate effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“… 7 , 8 In a recent study, we found that base editing could rapidly (within 48 h) and definitively treat a humanized mouse model of PKU with the PAH c.842C>T (p.Pro281Leu) variant when intravenously delivered in the form of mRNA and guide RNA (gRNA) encapsulated in lipid nanoparticles (LNPs) targeting the liver, where PAH mRNA is specifically expressed. 9 As little as 10% correction of the gene is sufficient to normalize blood Phe levels.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 8 In a recent study, we found that base editing could rapidly (within 48 h) and definitively treat a humanized mouse model of PKU with the PAH c.842C>T (p.Pro281Leu) variant when intravenously delivered in the form of mRNA and guide RNA (gRNA) encapsulated in lipid nanoparticles (LNPs) targeting the liver, where PAH mRNA is specifically expressed. 9 As little as 10% correction of the gene is sufficient to normalize blood Phe levels.…”
Section: Main Textmentioning
confidence: 99%
“…We also did not evaluate for the possibility of gRNA-independent off-target editing by SpRY-ABE8.8, wherein the deaminase domain of the base editor can spuriously deaminate genomic nucleic acid sequences independently of the Cas9 protein; notably, prior studies have suggested that this phenomenon is minimized when eighth-generation adenine base editors are delivered as mRNAs. 15 , 22 When SpRY-ABE8.8/PAH4 base editing for correction of the PAH c.1222C>T variant is compared against a similar base editing approach for correction of the PAH c.842C>T (p.Pro281Leu) variant, 9 also a frequent (albeit much less frequent) PKU variant, the former had substantially less potency in HuH-7 cells (EC 50 of 750 fmol/cell versus EC 50 of 64 fmol/cell), less editing activity in the mouse liver when delivered with the same LNP formulation at the same 2.5-mg/kg dose (mean desired on-target editing of 26% versus 39%), and more unwanted bystander editing in vivo (2.8% versus 0.8%). Finally, we did not perform a long-term mouse study, although the precedent of the LNP treatment for the PAH c.842C>T (p.Pro281Leu) variant resulting in durable normalization of blood Phe levels in PKU mice, through 6 months of observation, 9 suggests that SpRY-ABE8.8/PAH4 LNP treatment would be similarly durable.…”
Section: Main Textmentioning
confidence: 99%
“…PAH variant c.1066-11G>A, a splicing defect resulting in an in-frame insertion of 3 amino acids, is the second most common pathogenic variant causing PKU worldwide, prevalent in Southern Europe and Latin America. Innovative RNA-based therapeutics such as splice switching antisense oligonucleotides (Havens and Hastings, 2016) or HULC lncRNA mimics (Li et al, 2021), gene editing approaches (Böck et al, 2022; Brooks et al, 2023; Villiger et al, 2018) or use of specific pharmacological chaperones (Pey et al, 2008; Santos-Sierra et al, 2012), are theoretically applicable to target either the mutant pre-mRNA or the resulting protein, with the aim of correcting the pathological phenotype of this frequent variant. Due to the limitation in access to patients’ tissues where the PAH gene is expressed (liver and to a lesser extent, kidney) the splicing defect was studied using minigenes and in a gene edited HepG2 cells homozygous for the c.1066-11G>A variant, in which almost no detectable PAH protein and activity were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, base editing approaches, which have shown to be effective in correcting PKU variants in different mouse models (Böck et al, 2022; Brooks et al, 2023; Villiger et al, 2018), could provide a novel therapeutic approach for PKU patients with this specific variant. In this sense, the created avatar PKU mouse model with the "humanized" mutant (c.1066-11>A) intron 10 fragment of the endogenous Pah gene is an alternative preclinical model suitable for assessing the efficacy of adenine base editing as a therapeutic intervention which could be applicable to a high number of PKU patients worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of our effort over the last year has been developing gene editing technologies to correct the disease-causing mutations in patients with PKU. We've gotten a lot of traction with this, as it's been working well in cells and humanised mouse models ( Brooks et al, 2023 ). We've received a to take the PKU gene editing treatment to the clinic.…”
mentioning
confidence: 99%